2021
DOI: 10.3390/life11121383
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Framework to Evaluate the Effects of Anterior Cruciate Ligament Injury and Reconstruction on Graft and Cartilage Status through the Analysis of MRI T2 Relaxation Time and Knee Laxity: A Pilot Study

Abstract: Background: Anterior cruciate ligament (ACL) tear represents a common orthopedic traumatic issue that often leads to an early development of osteoarthritis. To improve the diagnostic and prognostic techniques involved in the assessment of the joint after the trauma and during the healing process, the present work proposes a multi-parametric approach that aims to investigate the relationship between joint function and soft tissue status before and after ACL reconstruction. Methods: Thirteen consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
(93 reference statements)
2
6
0
Order By: Relevance
“…Only few publications have assessed knee articular cartilage using qMRI shortly after anterior cruciate ligament (ACL) injuries. [49][50][51][52][53] Similar to our findings, lower T2 values have been observed shortly after ACL injury by Casula et al 49 in the knee cartilage. Studies by Marchiori et al 50 and Zhong et al 51 describe T2 relaxation time of knee cartilage after trauma, before ACL repair, but do not specify the time between the trauma and qMRI measurements.…”
Section: Discussionsupporting
confidence: 91%
“…Only few publications have assessed knee articular cartilage using qMRI shortly after anterior cruciate ligament (ACL) injuries. [49][50][51][52][53] Similar to our findings, lower T2 values have been observed shortly after ACL injury by Casula et al 49 in the knee cartilage. Studies by Marchiori et al 50 and Zhong et al 51 describe T2 relaxation time of knee cartilage after trauma, before ACL repair, but do not specify the time between the trauma and qMRI measurements.…”
Section: Discussionsupporting
confidence: 91%
“…We hypothesize that adjusting these measurements with respect to the body weight may lead to improved correlation strengths, as reported in an earlier study [40]. These results corroborate with few earlier studies [41, 42] that have suggested possible correlations between the T 2 * relaxation time for specific tissues like cartilage and meniscus and joint health in diseased conditions such as osteoarthritis or ACL related injuries.…”
Section: Discussionsupporting
confidence: 90%
“…In previous research, Biercevicz et al found that ACL graft volume and median signal intensity acquired from a T 1 ‐weighted sequence were associated with single‐leg hop test performance at 3‐ and 5‐year follow‐ups, as well as Knee Injury and Osteoarthritis Outcome Score (KOOS) quality of life, sport/function, pain, and symptom sub‐scores at 5‐year follow up, when the MR images were acquired at the same timepoints [4]. Marchiori et al found that T 2 relaxation time of the graft was correlated with arthrometric knee laxity at 4‐ and 18‐month follow up [28]. Once again, the T 2 relaxation time and arthrometric knee laxity were measured at the same timepoints, rather than between timepoints.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have suggested that the quantitative graft changes observed on MRI post‐ACL reconstruction (ACLR) are related to contemporaneous clinical, functional, and patient‐reported outcomes [4, 20, 23, 28, 34, 39, 44]. While these studies highlight the utility of qMRI outcomes in tracking patients’ response to ACL surgery, there is a lack of evidence as to whether qMRI measures of the ACL can be used to predict future clinical, functional, and patient‐reported outcomes after ACL surgery.…”
Section: Introductionmentioning
confidence: 99%